Penyelesaian Perkara Anak Berkonflik Dengan Hukum Melalui Diversi Pada Tahap Penyidikan Dalam Rangka Mewujudkan Keadilan Restoratif - Kayus Kayowuan Lewoleba; Yuliana Yuli Wahyuningsih (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
This study aims to analyze the settlement of cases of children in conflict with the law through a diversion approach at the investigation stage in order to realize restorative justice. . Diversion efforts at the investigation stage need to be carried out if cases of children in conflict with the law meet the requirements for diversion. Diversion means the granting of authority to law enforcement officials to take policy actions in dealing with or resolving the problem of child violations by not taking formal steps, including stopping or not continuing from the criminal justice process or returning it to the community. Or in other words, diversion is the transfer of a child's case from the criminal justice process to a process outside of criminal justice. This effort is carried out, especially in the investigation stage, which needs to be carried out in order to provide protection for children in conflict with the law, especially if the crime committed meets the diversion requirements. However, in reality in the field there are still many law enforcers, especially the police, who do not use this authority, this is due to various factors such as a lack of understanding from law enforcement officials regarding the treatment and handling of children in conflict with the law at every stage of the legal process. If diversion can be carried out early, it can prevent children in conflict with the law from having to go through all the long legal processes that can ultimately affect the child's psychological development. Diversion efforts are also in the context of realizing restorative justice which emphasizes recovery back to its original state rather than retaliation. The research method used is a juridical-normative approach with a statute approach and a conceptual approach. The results of the study conclude that firstly, for the best interests of the child, both as the perpetrator and the victim, it is necessary to make diversion efforts at the investigation stage if it meets the requirements to protect children. Second, the concept of diversion at the investigation stage experienced problems or was not carried out due to several factors such as the lack of understanding of law enforcement officials and the absence of agreement in the diversion deliberation.